Fast Regulation of Hormone Metabolism Contributes to Salt Tolerance in Rice (Oryzasativa spp. Japonica, L.) by Inducing Specific Morpho-Physiological Responses - Formentin, Elide; Barizza, Elisabetta; Stevanato, Piergiorgio; Falda, Marco; Massa, Federica; Tarkowskà, Danuše; Novák, Ondřej; Lo Schiavo, Fiorella (Plants (Basel, Switzerland), 2018)
Clear evidence has highlighted a role for hormones in the plant stress response, including salt stress. Interplay and cross-talk among different hormonal pathways are of vital importance in abiotic stress tolerance. A genome-wide transcriptional analysis was performed on leaves and roots of three-day salt treated and untreated plants of two Italian rice varieties, Baldo and Vialone Nano, which differ in salt sensitivity. Genes correlated with hormonal pathways were identified and analyzed. The contents of abscisic acid, indoleacetic acid, cytokinins, and gibberellins were measured in roots, stems, and leaves of seedlings exposed for one and three days to salt stress. From the transcriptomic analysis, a huge number of genes emerged as being involved in hormone regulation in response to salt stress. The expression profile of genes involved in biosynthesis, signaling, response, catabolism, and conjugation of phytohormones was analyzed and integrated with the measurements of hormones in roots, stems, and leaves of seedlings. Significant changes in the hormone levels, along with differences in morphological responses, emerged between the two varieties. These results support the faster regulation of hormones metabolism in the tolerant variety that allows a prompt growth reprogramming and the setting up of an acclimation program, leading to specific morpho-physiological responses and growth recovery.
Keywords: phytohormones; Oryza sativa; salt stress; RNA sequencing; phenotypic plasticity